Éléments pour une histoire de la recherche à l’École nationale supérieure du paysage de Versailles (ENSP) - Pierre Donadieu (Projets de Paysage)
The development of the organization of the research at the ENSP in Versailles is analyzed during the last forty years (1965 à 2005). In order to describe and interpret it, this text is based on the publications of the actors of this history and on the institutional contexts which have followed one to another.